2017
DOI: 10.1038/s41559-017-0226-3
|View full text |Cite
|
Sign up to set email alerts
|

Nodal–Activin pathway is a conserved neural induction signal in chordates

Abstract: Neural induction is the process through which pluripotent cells are committed to a neural fate. This first step of Central Nervous System formation is triggered by the "Spemann organizer" in amphibians and by homologous embryonic regions in other vertebrates. Studies in classical vertebrate models have produced contrasting views about the molecular nature of neural inducers and no unifying scheme could be drawn. Moreover, how this process evolved in the chordate lineage remains an unresolved issue. In this wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 43 publications
3
41
0
Order By: Relevance
“…Although at the onset of gastrulation amphioxus Chordin is indeed expressed in both dorsal mesoderm and ectoderm, this ectodermal Chordinexpressing region most likely contributes to the future posterior and trunk CNS due to the lack of extensive involution of tissues around the blastopore during amphioxus gastrulation (Zhang et al, 1997), which is in contrast to the Xenopus BCNE center that would eventually involute and contribute to most of the anterior CNS . In addition, a recent study showed that animal cap explants from early gastrula (G1) stage amphioxus embryos were not able to differentiate into CNS tissues autonomously (Le Petillon et al, 2017), suggesting that neural induction probably begins during gastrulation in the amphioxus embryos.…”
Section: Distribution Of Transcripts and The Activity Of Signaling Pamentioning
confidence: 99%
See 2 more Smart Citations
“…Although at the onset of gastrulation amphioxus Chordin is indeed expressed in both dorsal mesoderm and ectoderm, this ectodermal Chordinexpressing region most likely contributes to the future posterior and trunk CNS due to the lack of extensive involution of tissues around the blastopore during amphioxus gastrulation (Zhang et al, 1997), which is in contrast to the Xenopus BCNE center that would eventually involute and contribute to most of the anterior CNS . In addition, a recent study showed that animal cap explants from early gastrula (G1) stage amphioxus embryos were not able to differentiate into CNS tissues autonomously (Le Petillon et al, 2017), suggesting that neural induction probably begins during gastrulation in the amphioxus embryos.…”
Section: Distribution Of Transcripts and The Activity Of Signaling Pamentioning
confidence: 99%
“…Nodal signaling has been shown to play a major role in the DV axis determination in the amphioxus embryo (Le Petillon et al, 2017;Morov et al, 2016;Onai et al, 2010). At the start of gastrulation, both Nodal and Lefty are expressed in the dorsal region ( Fig.…”
Section: Nodal/vg1/activin Signaling Plays a Key Role In The Formatiomentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, monoclonal antibodies are costly and are not within the reach of a typical lab working in the area of evolutionary developmental biology. Commercially available antibodies produced for vertebrate research can in principle be used if directed against a highly conserved epitope shared by vertebrate and amphioxus protein.Currently, only antibodies against acetylated tubulin are routinely used (Le Petillon et al, 2017;Lu et al, 2012;Soukup et al, 2015;Vopalensky et al, 2012). A fairly small number of antibodies (all polyclonal) has so far been generated that specifically recognize amphioxus proteins in developing embryos (Vopalensky et al, 2012;Wu et al, 2011).…”
mentioning
confidence: 99%
“…Currently, only antibodies against acetylated tubulin are routinely used (Le Petillon et al, 2017;Lu et al, 2012;Soukup et al, 2015;Vopalensky et al, 2012). A fairly small number of antibodies (all polyclonal) has so far been generated that specifically recognize amphioxus proteins in developing embryos (Vopalensky et al, 2012;Wu et al, 2011).…”
mentioning
confidence: 99%